MiRNA Nomenclature: A View Incorporating Genetic Origins, Biosynthetic Pathways, and Sequence Variants. Issue 11 (November 2015) - Desvignes, T.; Batzel, P.; Berezikov, E.; Eilbeck, K.; Eppig, J.T.; McAndrews, M.S.; Singer, A.; Postlethwait, J.H.
Abstract : High-throughput sequencing of miRNAs has revealed the diversity and variability of mature and functional short noncoding RNAs, including their genomic origins, biogenesis pathways, sequence variability, and newly identified products such as miRNA-offset RNAs (moRs). Here we review known cases of alternative mature miRNA-like RNA fragments and propose a revised definition of miRNAs to encompass this diversity. We then review nomenclature guidelines for miRNAs and propose to extend nomenclature conventions to align with those for protein-coding genes established by international consortia. Finally, we suggest a system to encompass the full complexity of sequence variations (i.e., isomiRs) in the analysis of small RNA sequencing experiments. Trends: Functional miRNAs can originate from various types of noncoding RNA genes. The definition of miRNAs should take a functional perspective. The full complexity of isomiR populations should be considered in miRNA studies. miRNA nomenclature systems should encompass origins, function, and isomiRs.